The Mediating Effect of EPS on the Relationship between ROE and Stock Prices of 15 Banks Listed on Indonesia Stock Exchange - Francis Hutabarat; Mega Sari (Journal of Applied Business and Technology, 2020)
This research is descriptive which collects and presents data from financial statements from 2014 - 2018 by taking ROE and EPS data as independent variables and stock prices as the dependent variable. Measurement scales used statistical scales such as regression analysis test, f test, and t-test. The results showed that 15 bank sector companies as a place of this research had good management performance and performed their functions well, it can be seen from the ratio of ROE and EPS. From the test results based on the regression analysis test, f test, and t-test, the results are obtained that the contribution of ROE to changes in the Stock price is 25.8%, with EPS mediation, the contribution of ROE and EPS to changes in the Stock price is found to be 47.2% and the change in the value of R-Square change of 0.219 or 21.9%. Significant test results indicate a significant effect between ROE on Stock prices. This can be seen from the F-test value of 26,668 and significant value of 0,000 at α = 0.05 or 5% and with the presence of EPS mediation, the effect of ROE and EPS on the stock price is significant with a significant level of 0,000 at α = 0.05 or 5% with F -The existence of EPS mediation, it was found that ROE and Stock’s Prices have a significant effect of 0.019 at a significant level of 5%. Thus any change in ROE will change to an increase in Stock Price by 0.236 significantly.Therefore, because ROE and the Stock price have significant value, EPS does not fully mediate the effect of ROE and the stock pricetest 34,129.